Populist radical right parties in Europe - Mudde, Cas; Cambridge eBooks (Cambridge : Cambridge University Press, 2007)
As Europe enters a significant phase of re-integration of East and West, it faces an increasing problem with the rise of far-right political parties. Cas Mudde offers the first comprehensive and truly pan-European study of populist radical right parties in Europe. He focuses on the parties themselves, discussing them both as dependent and independent variables. Based upon a wealth of primary and secondary literature, this book offers critical and original insights into three major aspects of European populist radical right parties: concepts and classifications; themes and issues; and explanations for electoral failures and successes. It concludes with a discussion of the impact of radical right parties on European democracies, and vice versa, and offers suggestions for future research.
I: Concepts -- Constructing a conceptual framework -- From conceptualization to classification : which parties? -- II: Issues -- Who's afraid of--? -- Männerparteien -- It's not the economy, stupid! -- Populist radical right democracy -- "Europe for the Europeans" -- Globalization : the multifaced enemy -- III: Explanations -- Demand-side : in search of the perfect breeding ground -- External supply-side : political opportunity structures -- Internal supply-side : the populist radical right party -- Assessing impact : populist radical right parties vs. European democracies -- Conclusions.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Political parties -- Europe; Conservatism -- Europe; Populism -- Europe; Right and left (Political science); Europe -- Politics and government -- 1945-; Electronic books